Modelling the current and future agro-ecological distribution potential of Mexican prickly poppy (Argemone mexicana L.) invasive alien plant species in South Wollo, Ethiopia - Teklegiorgis, Shewakena; Belayneh, Anteneh; Gebermeskel, Kidane; Akomolafe, Gbenga Festus; Dejene, Sintayehu W. (Informa UK Limited, 2025)
Argemone mexicana L. is an invasive alien plant species (IAPS) that belongs to Papaveraceae family. This study aimed to identify and map its current and future (2050 and 2070) potential distribution in South Wollo, Ethiopia. Eight Kebeles were selected using a stratified random sampling method that covered two agro-ecologies ranging 1500–3200masl for species presence data collection and 204 presences data were used for modelling. Climate, topography, and land use land cover change (LUCC) variables were used to build the species distribution model (SDM). An ensemble SDM model was run consisting of five algorithms into one single model. The area under the curve (AUC) and true skill statics (TSS) of the ensemble SDM score values of 0.89 and 0.7, respectively. The predicted result on its agro-ecological distribution showed 76.75% was non-suitable and 23.26% was suitable in varied extents, currently. Suitability will be increased after LUCC and climate change except the SSP5–8.5 2070 emission scenario. It will be highest under SSP1–2.6, 2050, and SSP2–4.5, 2070 emission scenarios possessing 28.67% and 28% suitability class, respectively. A. mexicana distributed in the mid and highland agro-ecologies from 1500–3200masl both in current and future time period. It urges effective coordination among actors to minimize its distribution potential.